Increased natural killer cell subsets with inhibitory cytokines and inhibitory surface receptors in patients with recurrent miscarriage and decreased or normal subsets in kidney transplant recipients late post-transplant - Zhu, Li; Aly, Mostafa Gaafa; Morath, Christian; Kuon, Ruben-Jeremias; Ekpoom, Naruemol; Opelz, Gerhard; Daniel, Volker (Clinical & experimental immunology, 2018)
Patients with recurrent miscarriage (RM) show up-regulated cytotoxic natural killer (NK) cells that are suspected to play a causal role in abortion. In the present study, we investigated counter-regulating inhibitory mechanisms and compared the results in RM patients with those of healthy controls (HC), patients with end-stage renal disease (ESRD) and kidney transplant recipients late post-transplant (TX). NK, NK T and T cell subsets were analysed in the peripheral blood of 31 RM, 14 female ESRD and nine female TX patients as well as 21 female HC using eight-colour fluorescence flow cytometry. Compared with HC, RM patients showed significantly higher absolute numbers of CD56+ NK cells co-expressing the phenotype interferon (IFN)-γR+, IL-4+, transforming growth factor (TGF)-β+, IL-4+ human leucocyte antigen D-related (HLA-DR)+, TGF-β+HLA-DR+, IL-4+TGF-β+, IL-4+TGF-β-, IFN-γ+ and/or IL-10-IFN-γ+ (all P ≤ 0·01), more IL-17+CD56bright (P = 0·028) NK cells and more CD56dimCD16+ NK cells co-expressing IFN-γR, IFN-γ, IL-4 and/or TGF-β (all P ≤ 0·01). When the same cell subsets were analysed in ESRD or TX patients, cytokine-producing NK cell subsets were not significantly different from those of HC. RM patients showed significantly higher absolute numbers of CD158a+, CD158b+, CD158a-CD158e+ (all P < 0·05), NKG2D+NKG2A+, NKG2D +NKG2A-, NKG2D+ and/or NKG2A+ (all P ≤ 0·01) CD56+ NK cells and higher CD158a+, CD158b+ (all P < 0·05), NKG2D+ and/or NKG2A+ (all P < 0·01) CD56dim+CD16+ NK cells than HC. In contrast, ESRD patients had normal and TX recipients had lower CD158a+ and NKG2D+NKG2A-CD56+ NK cells and lower CD158a+CD56dim+CD16+ NK cells (all P < 0·05) than HC. RM patients have abnormally high circulating NK cells expressing inhibitory cytokines and inhibitory surface receptors which might contribute to the pathogenesis of RM.
Gesehen am 02.04.2020